2012
DOI: 10.1039/c2dt30631j
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside-5′-phosphorothioate analogues are biocompatible antioxidants dissolving efficiently amyloid beta–metal ion aggregates

Abstract: Amyloid beta (Aβ) peptide is known to precipitate and form aggregates with zinc and copper ions in vitro and, in vivo in Alzheimer's disease (AD) patients. Metal-ion-chelation was suggested as therapy for the metal-ion-induced Aβ aggregation, metal-ion overload, and oxidative stress. In a quest for biocompatible metal-ion chelators potentially useful for AD therapy, we tested a series of nucleoside 5'-phosphorothioate derivatives as re-solubilization agents of Cu(+)/Cu(2+)/Zn(2+)-induced Aβ-aggregates, and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 53 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…Amyloid-beta (1e42) oligomers were prepared according to Amir et al [10]. Briefly, Ab 42 (3 mg) was dissolved in 10 mM NaOH, sonicated for 3 min, and then freeze-dried.…”
Section: Evaluation Of the Effect Of Nucleotide Analogues On Primary mentioning
confidence: 99%
See 3 more Smart Citations
“…Amyloid-beta (1e42) oligomers were prepared according to Amir et al [10]. Briefly, Ab 42 (3 mg) was dissolved in 10 mM NaOH, sonicated for 3 min, and then freeze-dried.…”
Section: Evaluation Of the Effect Of Nucleotide Analogues On Primary mentioning
confidence: 99%
“…The purine nucleotide scaffold contains metal binding sites at both the phosphate chain and purine ring (N7-nitrogen atom), and makes a natural divalent metal ion chelator [8]. Indeed we showed that nucleotides are efficient Fe(II)-chelators [10].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some experiments also find that the level of metal ions in AD patients are 3-7 folds higher than that of healthy individuals [10], it indicated that the dyshomeostasis of biometals (Fe, Cu, Zn) in the brain may contribute to AD pathology [11]. Clioquinol (a classic metal chelator used as antifungal drug and antiprotozoal drug), had been tested to treat AD [12,13]. The phase II clinical trials suggested that clioquinol could halt cognitive decline in AD, possibly owing to its ability to chelate copper and zinc ions.…”
Section: Introductionmentioning
confidence: 99%